WORDS BEHIND MASK: COMPARING COPYRIGHT PROTECTION FOR PSEUDONYMOUS AUTHORS IN INDONESIA AND AUSTRALIA - Karina Josephine Siregar; Aurora Jillena Meliala (RADJA PUBLIKA, 2025)
This article discusses the regulation of copyright protection for pseudonymous authors from a comparative perspective between Indonesia and Australia, focusing on the fulfillment of moral and economic rights. Using a normative juridical and comparative approach, this study examines the legal gap within the Indonesian system of moral rights and economic rights of works created by authors with concealed identities. Although Article 5 of the 2014 Copyright Law recognizes pseudonymous authors, its implementation remains weak due to the absence of explicit enforcement mechanisms. On the other hand, Australia clearly separates moral rights and economic rights and adopts a statutory presumption approach to recognize and protect pseudonymous authors. However, implementing the Australian model in Indonesia faces limitations, primarily because Indonesia’s legal culture has yet to be deeply rooted in public consciousness. This study proposes context-based adaptations, such as confidential registration and the strengthening of publishing agreements, as alternative solutions. By integrating cultural values and the national legal structure, this article emphasizes the importance of localizing copyright protection to align with the legal and social characteristics of Indonesian society, while also promoting the development of a safe and inclusive literacy ecosystem for pseudonymous authors in the future.